KEDUDUKAN FRAKSI DI DEWAN PERWAKILAN RAKYAT BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2014 TENTANG MPR, DPR, DPD, dan DPRD - Yuswanto '; Mexsasai Indra; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In the Constitution of the Republic of Indonesia Year 1945 does not regulate the establishment of factions in parliament, either implicitly or explicitly. But the mention of designations governed by Act No. 17 of 2014. The fraction is called as containers assembled House of Representatives, where in Law Number 17 Year 2014 About the People's Consultative Assembly, the House of Representatives, Regional Representatives Council, and the Council of Representatives People's Region, in teologistujuan in fraction form basically for optimizing tasks, functions, rights and authority of the House of Representatives, but in the Act the authority of the fraction is not clearly regulated so ambiguous. The existence of factions in the House of Representatives just as political representation because pembentukanya only by the configuration of political parties not based constituencies, interests and talents. The shadows of the dominance of the fraction against the sovereignty of members of the House of Representatives more apparent when the authority which is owned by a fraction so great but the existence and function is unclear. So that the position of the factions in the House of Representatives only raises the pros and cons of which the existence of factions just as inhibiting the performance of members of the House of Representatives as a State Institution.Results of research can be concluded: first, that the urgency of the formation of factions in the House of Representatives based on Law Number 17 Year 2014 About the eople's Consultative Assembly, the House of Representatives, Regional Representatives Council, and Regional House of Representatives is to optimize the execution of the functions, powers, and the Board of Representatives. Both factions grouping ideally not by political parties but by constituencies, interests and talents. Suggestions author: First, the government is expected to dissolve the factions in the House of Representatives and maximize fittings council. Second, the government is expected to limit the authority of the factions not to exceed the authority of the board of the existing fittings in the House of Representatives.Keywords: Position - Faction - House of Representatives